Identification of the Diversity of Morphological Characteristics of Some Local Upland Rice Cultivars in East Aceh - Retno Ryandini; Syukri Risyad (Talenta Publisher, 2024)
It is important to characterize the traits of local cultivars both morphologically, physiologically, and genetically. Characterization is a process aimed at identifying important traits economically valuable and beneficial for agriculture or determining the relevant characteristics varieties. The objective of this study was to determine the diversity of several local upland rice cultivars from East Aceh and identifying the morphological characteristics of these cultivars. The research was conducted over 4 months, from October to February 2023, at the experimental field of the Faculty of Agriculture, Samudra University, Langsa City, Aceh, with an elevation of approximately 10 meters above sea level and a soil pH of 5.9. The study used data from both qualitative and quantitative traits, which were tabulated and then analyzed for kinship relationships using IBM SPSS software with hierarchical clustering analysis using Euclidean distance. The results indicated that the testing of several local upland rice cultivars from East Aceh, based on morphological characterization, showed differences in the number of tillers, flower characteristics, panicles, and leaf traits. However, there were no differences plant height, number of productive tillers, leaf blade color, and 1000-grain weight when observing grain weight. Differences in growth and production characteristics were due to interactions between genetic and environmental factors, leading to variability in traits among the tested cultivars. Based on the morphological characteristics of the 10 local upland rice cultivars from East Aceh, the Ramos Gunung and Sibontot cultivars were found to be among the most promising for development due to their highest production yields compared to other cultivars.